Strategi Pemberdayaan untuk Kesejahteraan dan Kemandirian Kaum Dhuafa - Alfira Assyha Ramadanty; Muhtadi Muhtadi (UIN Siber Syekh Nurjati Cirebon, 2023)
This research is about the empowerment strategy carried out by the Rindang Indonesia Foundation for the poor through computer training programs. The research method used is descriptive qualitative method with data collection techniques using interviews, observation and documentation. The results of this study indicate that the empowerment strategies carried out by the Rindang Indonesia Foundation include human resource development, group institutional development, community investment, productive business development, and providing the right information. Indicators of the success of the empowerment program are measured by reducing the number of poor people, namely reaching more than 10 (ten) people and 2 (two) others successfully working in the company, business development to increase income, namely 10,000 / pcs, increasing community awareness, increasing group independence, and increasing community capacity and income distribution.